Costeffective formulation of bio-fertilizer using agricultural residues as carriers and determination of shelflife of bio-fertilizer inoculants (Dhaka University Journal of Biological Sciences, 2023)
Traditionally, inorganic chemical-based fertilizers is used for soil management strategies, which can cause public health and environmental threats. Alternatively, bio-fertilizer can be used to increase the productivity and sustainability of soil without causing environmental pollution. The present study aimed to cost-effectively produce bio-fertilizer using agricultural residues and determine the shelflife and efficacy of the bioinoculants. We used sterilized rice husk ash and alluvial soil (1:2) to prepare cost-effective carriers. Rhizobium sp., Azotobacter sp., and Trichoderma sp. were grown in a newly designed culture medium for economic production as bio-inoculants. The efficacy of the formulated bio-fertilizer was tested on a small scale, where it significantly improved the growth of the sponge gourd (Luffa aegyptiaca) plant (p